PENGARUH SUPERVISI AKADEMIK DAN DISIPLIN KERJA KEPALA SEKOLAH TERHADAP KINERJA GURU SEKOLAH DASAR - Ivan Agustinus; Sukmawati Sukmawati; M. Syukri (Universitas Tanjungpura, 2019)
AbstractThis study uses a quantitative approach that is descriptive correlational. The use of this approach is based on the consideration that this study researchers want to see the effect of academic supervision and principals' work discipline on teacher performance in the Sungai Raya Kepulauan District Elementary School. The population used was all elementary school teachers throughout Sungai Raya Kepulauan District with a sample of 63 people. This study uses the distribution of questionnaires / questionnaires as data collection techniques.Research Results: Data analysis techniques are described using univariate and multivariate. Univariate results from 63 respondents, most of the academic supervision was ineffective (41.3%), most of the work discipline was in the good category (42.9%) and most of the teacher's performance was in the good category (50.8%). Multivariate results explain that based on the hypothesis test using partial correlation coefficient that there is a conclusion that there is no effect of academic supervision on teacher performance at SD Bengkayang (sig. 0.309> 0.05). Furthermore, there is the influence of work discipline on teacher performance in SDN throughout Sungai Raya Kepulauan District, Bengkayang Regency (Sig. 0,000 <0,05). Based on the value of R Square of 0.900, it can be said that the contribution of academic supervision and work discipline together towards teacher performance is 90%.Conclusion Based on the results of the study that work discipline influences teacher performance but there is no influence of academic supervision on teacher performance in SD Sungai Raya Kepulauan District. Suggestions submitted are the need to make efforts to disseminate information and provide information before conducting a performance assessment so that the expectations of the principal are fulfilled according to the school's vision and mission. Keyword: Discipline, Performance, Supervision and Teacher